CAS '99 Proceedings. 1999 International Semiconductor Conference (Cat. No.99TH8389)
DOI: 10.1109/smicnd.1999.810443
|View full text |Cite
|
Sign up to set email alerts
|

Image of phonon spectrum in the 1/f noise of semiconductors

Abstract: features noise peaks which develop at some specific temperatures. We compared this noise structure with either phonon density of states or Raman spectrum of each topological insulator (TI), respectively. In (BiSb)2Te3, the comparison revealed that the noise peaks track the van Hove singularities in the phonon density of states. It resulted that bulk atomic oscillators are responsible for the noise peaks. The most intense noise peak observed in (BiSb)2Te3 at 50 K is attributed to the thermal motion of the Bi at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 75 publications
(137 reference statements)
0
2
0
Order By: Relevance
“…Hence, the intermittent g-r process generating 1/f noise is also phonon-induced. Indeed, there is ample empirical evidence that electronphonon scattering is the dominate mechanism generating 1/f noise in semiconductors [13][14][15]. As was already mentioned in a previous paper [19], this suggests that the intermissions (= off-states) originate from phonons due to an unknown mechanism.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Hence, the intermittent g-r process generating 1/f noise is also phonon-induced. Indeed, there is ample empirical evidence that electronphonon scattering is the dominate mechanism generating 1/f noise in semiconductors [13][14][15]. As was already mentioned in a previous paper [19], this suggests that the intermissions (= off-states) originate from phonons due to an unknown mechanism.…”
Section: Resultsmentioning
confidence: 82%
“…Based on empirical findings, Hooge, Kleinpenning and Vandamme [13] concluded that 1/f noise is a bulk phenomenon; they favor phonon scattering as an origin of 1/f noise. This perspective is also supported by Mihaila [14] who claims that 1/f noise comes from the perpetual equilibrium atomic motion. Musha, Gabor and Minoru [15] investigated the scattering of laser light in quartz and found 1/f fluctuations in the number of phonons.…”
Section: Introductionmentioning
confidence: 74%